Methodology of Teaching the Typology and Genesis of Kazakh Kui: Foreign Experience and National Peculiarities - Aigul , Assan; Gaukhar, Baltabayeva; Erzhan , Ergeshov; Serikkazy , Korabay; Alimgazy , Daulekhanuly; Zhanat, Bisenbayeva (Journal of Ecohumanism, 2024)
Kazakh kui, a distinctive genre of traditional music, holds an essential place in the cultural heritage of Kazakhstan. The typology and genesis of Kazakh kui, with its vast history and complex forms, present a unique educational challenge for both local and international scholars. This research aims to analyze the methodologies of teaching the typology and genesis of Kazakh kui by comparing foreign pedagogical models with national peculiarities. Specifically, it examines how international methods of music education can inform the teaching of Kazakh kui, while also highlighting the significance of preserving local cultural traditions. The study explores the typology of Kazakh kui, identifying different types such as instrumental, vocal, and mixed forms, and traces the genesis of the genre, considering its origins in Kazakh nomadic culture and its evolution through the centuries. The paper also looks at existing pedagogical frameworks within Kazakhstan and abroad, comparing how Kazakh kui is taught in various contexts. Additionally, the research investigates the challenges and opportunities presented by these foreign methodologies when applied to the national context of Kazakhstan, with an emphasis on developing educational practices that reflect both modern and traditional approaches. Finally, the study aims to offer recommendations for a comprehensive and culturally respectful methodology for teaching Kazakh kui, considering both its historical significance and contemporary relevance.